Non-drug treatment of type II diabetes literature review (International Seven Journal of Health Research, 2023)
Diabetes Melitus (DM) has become a major global public health problem and is growing every year. DM is divided into two types. Type II is the most common and will be explored in this article in an exploratory literature review regarding its non-drug treatment. Articles were explored in databases such as PubMed, Scielo and Scopus and reviewed using texts with scientific relevance. We researched the different origins of this chronic disease, considered multifactorial, and described its non-drug treatments, grouping them into: Treatments with physical activities, dietary measures and other alternatives. We conclude that your treatment is personalized and should not include just one therapy. One of the best strategies for treating DM II is self-management. Patients who control their eating habits and physical activity experience a great improvement in their quality of life, as individuals who are well informed about their diet tend to make choices that are more appropriate to their health. Our article concludes that the non-pharmacological treatment of DM II must have an eclectic and multidisciplinary approach.